2011
DOI: 10.1007/s11517-011-0797-0
|View full text |Cite
|
Sign up to set email alerts
|

Advances in upper limb stroke rehabilitation: a technology push

Abstract: Strokes affect thousands of people worldwide leaving sufferers with severe disabilities affecting their daily activities. In recent years, new rehabilitation techniques have emerged such as constraint-induced therapy, biofeedback therapy and robot-aided therapy. In particular, robotic techniques allow precise recording of movements and application of forces to the affected limb, making it a valuable tool for motor rehabilitation. In addition, robot-aided therapy can utilise visual cues conveyed on a computer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(113 citation statements)
references
References 91 publications
0
105
0
8
Order By: Relevance
“…Over the past decade several studies have emerged looking at the use of highly sophisticated technologies, such as robotics and virtual reality to tap into the needs of clinicians and patients [27]. Although traditional physiotherapy coupled with machine mediated therapy can be beneficial in the recovery process, once patients are discharged from hospital it is difficult to exercise correctly the affected limb without the support from clinicians.…”
Section: Existing Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the past decade several studies have emerged looking at the use of highly sophisticated technologies, such as robotics and virtual reality to tap into the needs of clinicians and patients [27]. Although traditional physiotherapy coupled with machine mediated therapy can be beneficial in the recovery process, once patients are discharged from hospital it is difficult to exercise correctly the affected limb without the support from clinicians.…”
Section: Existing Systemsmentioning
confidence: 99%
“…In general these systems can be grouped according to the rehabilitation principle they follow [28]: (i) treadmill gait trainers, (ii) foot-plate-based gait trainers, (iii) overground gait trainers, (iv) stationary gait trainers, (v) ankle rehabilitation systems (stationary systems and active foot orthoses). The description of a number of upper limb rehabilitation devices can be found in [27,29,30].…”
Section: Existing Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown a positive effect of gameplaying on therapy outcome by increasing motivation. Latest works, like Guidali [7], with those devices involve the application of virtual reality to train activities of daily living.…”
mentioning
confidence: 99%